Solidarity of UMPSA international students from 13 countries participating in the International SDG Run for sustainable development goals - MUHAMMAD ZUFLI, ZUHARI (UMPSA, 2024)
KUANTAN, 8 June 2024 - The Pahang International SDG Run Program organised by the Centre for International Relations (CIR), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) together with the Pahang State Kelana Scout Secretariat was held at Pantai Sepat, Kuantan on the last weekend.